Early signs of thaumasite formation in calcined clay-limestone cement: Short-term changes of the hydrate phase assemblage - Schlage Katarina K.; Ottosen Lisbeth M.; Kunther Wolfgang (MATEC Web of Conferences)
To reduce CO2 emissions associated with cement production, the use of calcined clay and limestone has gained increasing attention as supplementary cementitious materials. However, the addition of limestone can potentially compromise the lifetime of a structure due to the risk of thaumasite formation. Thaumasite is stable only at low temperatures and forms when cement is exposed to sulphate-rich environments such as seawater. This study investigates the early signs of thaumasite formation and other hydration phase changes in calcined clay-limestone cement at 5 °C. Cement samples containing 35 % calcined clay or limestone were exposed to a 0.3 % Na2SO4 solution simulating the SO32- concentration in the Femern Belt, Denmark, with a solution-to-cement mass ratio of 1:100, to create conditions optimal for the formation of thaumasite. The samples were analysed using X-ray diffraction and thermogravimetric analysis. The study focuses on early changes in the phase assemblage to provide insights into the sulphate resistance of calcined clay-limestone cement. By identifying the early changes, the aim is to screen several binders and gain a better understanding of the durability of calcined clay-limestone cement when exposed to sulphate-rich environments. The screening focuses on processes that might be limited by the low exposure concentrations used in this study.